Let's Get It On: Dressing Skill Development in Children With Vision Impairment and Children With Down Syndrome - Hayton, Jessica; Wall, Karl; Dimitriou, Dagmara (Frontiers in Education, 2019)
Dressing is a fundamental independent living skill often haphazardly acquired via visual observation. For children with vision impairment and children with Down Syndrome (where vision impairment is a component), dressing skill acquisition can be delayed due to a reduced/absent visual modality. Independent living skills is an aspect of habilitation practice and training, designed to maximise independence in children and young people with vision impairment and prepare them for adulthood. This paper, presented in two parts, first details a systematic (UK based) survey exploring fastening use across a clothing sample of birth-adult clothing (N=12,967). Study 1 presents a frequency distribution exploring types of fastenings used on clothing items from birth-adulthood. The data are fundamental in exploring the likelihood of fastening exposure across developmental phases. Further, Study 1 details the process behind developing a novel dressing skill intervention. Informed by Study 1, Study 2 qualitatively explored the effectiveness of an original resource/group-based intervention over a 10-week period. Eighteen children were recruited for the study, namely children with vision impairment (n=9) and children with Down Syndrome (n=9) aged 5-11 years. Collective and illustrative case studies are presented based on emergent themes from intervention observations. The findings reveal areas for consideration by Habilitation Specialists and the multidisciplinary team surrounding children with vision impairment and/or Down Syndrome as this may inform Habilitation Plans, and Educational Health Care Plan reports. The implications of this study extend beyond dressing skill development in children with vision impairment and/or Down Syndrome and inform resource development and subsequent practice when working with children with special educational needs and disabilities.